An empirical investigation of the loan concentration risk in Latin America - Kalotychou, Elena; Staikouras, Sotiris (My University, 2006)
The paper sets out to explore the factors affecting the credit quality of the Latin American region. Specifically, a logit framework is employed based on macroeconomic and financial data to determine the causes of Latin American debt crises in the last two decades. The analysis uses a modification of the default indicator to explicitly incorporate country arrear capacity. A number of domestic and international signals are found to be important in determining earlier as well as recent incidents. Domestic fundamentals, however, bear a much heavier weight than global conditions, implying that policy-makers still enjoy some freedom in preventing crises by monitoring country vulnerability. Furthermore, the study focuses on the out-of-sample classification accuracy of the proposed estimator using various criteria and provides 1-, 2- and 3-year-ahead forecasts for country default probabilities. Predictive performance is satisfactory with a reasonable reduction in accuracy in the out-of-sample period. Nevertheless, the findings indicate an upward bias towards type II errors.
Keywords: Financial crises; Forecasting; International credit risk; Logit modelling